Giving the hostel mess a miss: investigating students’ attitude and behaviour towards mess and skipping mess meals, using the theory of planned behaviour - Pravin Dange; Chanakya Kumar (International Journal of Adolescence and Youth)
The ‘hostel mess food’ provides for both economy and health. Yet, a significant number of students miss their scheduled meals at the mess to eat outside food. This is a significant concern for mess managers, university authorities, and parents. Understanding the antecedents of the mess meal skipping behaviour is crucial to design interventions to promote healthier eating habits and optimize mess utilization. This study investigates these antecedents using the theory of planned behaviour and employs the Structural Equation Modelling (SEM) technique to analyse the data collected from Hostel Students of a prominent Pune (India) based Higher Education Institution. The study reveals that the attitude towards mess food negatively influences mess meal skipping behaviour. Subjective norms significantly impact mess food skipping behaviour and moderate the influence of Perceived Behavioural Control on meal skipping behaviour. For mess managers, it entails focusing on subjective norms-based interventions to influence the mess meals skipping behaviour.